2007
DOI: 10.1162/jocn.2007.19.4.642
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Perceptual Features in Logical Reasoning: A Parametric Functional Magnetic Resonance Imaging Study

Abstract: Abstract& Participants experience difficulty detecting that an item depicting an H-in-a-square confirms the logical rule, ''If there is not a T then there is not a circle.'' Indeed, there is a perceptual conflict between the items mentioned in the rule (T and circle) and in the test item (H and square). Much evidence supports the claim that correct responding depends on detecting and resolving such conflicts. One aim of this study is to find more precise neurological evidence in support of this claim by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 43 publications
7
58
1
Order By: Relevance
“…A recent series of results (Monti et al, 2007(Monti et al, , 2009Rodriguez-Moreno and Hirsch, 2009) nonetheless suggests that language areas are not involved in the deductive process, a finding consistent with several previous reports (Canessa et al, 2005;Fangmeier et al, 2006;Goel and Dolan, 2001;Knauff et al, 2002;Noveck et al, 2004;Parsons and Osherson, 2001;Prado and Noveck, 2007). We interpret these findings as implying that the role of language is confined to initial encoding of verbal statements into mental representations suitable for the inferential calculus.…”
Section: Deduction As a Language Based Processsupporting
confidence: 91%
“…A recent series of results (Monti et al, 2007(Monti et al, , 2009Rodriguez-Moreno and Hirsch, 2009) nonetheless suggests that language areas are not involved in the deductive process, a finding consistent with several previous reports (Canessa et al, 2005;Fangmeier et al, 2006;Goel and Dolan, 2001;Knauff et al, 2002;Noveck et al, 2004;Parsons and Osherson, 2001;Prado and Noveck, 2007). We interpret these findings as implying that the role of language is confined to initial encoding of verbal statements into mental representations suitable for the inferential calculus.…”
Section: Deduction As a Language Based Processsupporting
confidence: 91%
“…The activation of the ACC was probably related to the detection of such conflict between empirical beliefs and the logical rules in the ICMT conditional argument, as suggested by previous literature [6] . Additionally, other studies found increased ACC activity when perceptual information conflicted with the logical conclusion of conditional arguments [13,14] .…”
Section: Discussionmentioning
confidence: 88%
“…A defining property of the dual process model of reasoning is that the analytic system is able to inhibit and override the heuristic system so that individuals can successfully carry out logical tasks 48,49,50 . Neuroimaging work on logical and scientific reasoning in adults has consistently shown that the inhibition of pre-existing beliefs, misleading perceptualbiases, and intuitive heuristics is associated with the activation of the anterior cingulate cortex (ACC) and the prefrontal cortex, notably the inferior frontal cortex (IFG) and dorsolateral prefrontal cortex (DLPFC) 10,11,25,26,48 .…”
Section: Conceptual Knowledge In the Brainmentioning
confidence: 99%